Bourbon's Backroads : A Journey through Kentucky's Distilling Landscape - Raitz, Karl B. (Book collections on Project MUSE., 2019)
This book is about one of Kentucky's signature industries, whiskey distilling. It is also about the landscape that the industry created and the heritage that the landscape represents. The book can be read in the traditional way; simply retire to an arm chair and read about how distillers made that bright amber liquid in the cut glass tumbler standing on your side table. Or, one can use the book as a guide to visit and experience the places where bourbon's heritage was made; distilleries long standing, relict, razed, or brand new; distiller's homes on Main Street, villages and neighborhoods where laborers lived, storage warehouses on Whiskey Row, river landings and railroad yards, and factories where copper distilling vessels and charred white oak barrels are made. Reading the story of fine bourbon distilling can be engrossing; standing in the landscape where it began and continues to thrive is akin to participating in an interactive theater performance! --